Penerapan Pembelajaran TaḥfῙẓ Al-Qur’an Melalui Metode Ummi Dalam Meningkatkan Kualitas Hafalan Al-Qur’an Siswa - Khojanah, Siti; Pahrurroji, Pahrurroji (Prodi Pendidikan Keagamaan Islam, 2024)
Memorizing the Qur'an (TaḥfῙẓ Al-Qur'an) became a trend among the people. It can be seen from the increasing activities of Musābaqah Ḥifẓ Al-Qur'an both at the international and national levels. This study aims to determine the application of taḥfῙẓ learning with the ummi method and instructor strategies in improving the quality of student memorization at SDIT Al-Hikmah Pamulang South Tangerang. This research uses a qualitative approach with a descriptive type of research. The location of the research was conducted at SDIT Al-Hikmah Pamulang, South Tangerang. The main data sources of the study were school principals, Qur'an coordinators, taḥfῙẓ instructors, 4th grade students. Data collection techniques include observation, interviews, and documentation. While the data analysis techniques used are data collection, data reduction, and data conclusion. The results of this study show that the application of learning taḥfῙẓ Al-Qur'an through the ummi method in improving the quality of student memorization at SDIT Al-Hikmah can be seen from various aspects. First, the aspect of artificiality in reading the Qur'an of students. Second, the memorization aspect can be seen from the increasing number of memorization and the better quality of memorization. Third, the discipline aspect.